Re-Investigating the Roles of Green Service-scape to Improve Tourism Performance Marketing Service Dominant Logic Perspective: A Literature Review - Simanjuntak, Mariana; Rumondang Banjarnahor, Astri (Quantitative Economics and Management Studies, 2021)
This study aims to investigate previous research on the co-creation of Green Service-scape Destination (GSD) specifically concerning definitions, theories used, research themes, methodologies, and contexts; studied in accordance with the perspective of Service Dominant Logic (SDL). This study used bibliometric analysis and used Publish or Perish software with Google Scholar as the database. A total of 183 articles published in 122 journals from 2010 to 2020 were selected. This study used systematic data to reveal trends in development markets and qualitative inductive analysis to define relevant themes within the topic. Search results according to keywords, found that the total number of research articles there are 1246, with the most cites themed SDL totally 910. This study provides future directions for research on GSD. GSD generates increased variety of tourist needs through proactive green innovation activities in efforts to adjust services. GSD provides improved methods, types, quality and service design with green environmental conditions, resources and service provider corporate support. To get the maximum advantage of layout and atmosphere is given added value through Innovation. This study reveals trends in co-creation GSD and sustainable marketing performance has the potential to generate job opportunities, empower resources effectively and strategically, increase social expectations and awareness, improve the economy and meet the needs of destinations and the sustainability of a value chain.